2011
DOI: 10.1016/j.jcrs.2010.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Visual function and spectacle independence after cataract surgery: Bilateral diffractive multifocal intraocular lenses versus monovision pseudophakia

Abstract: Bilateral multifocal IOLs and conventional monofocal IOL pseudophakic monovision significantly improved spectacle independence and visual quality-of-life measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 15 publications
5
44
1
5
Order By: Relevance
“…Increasingly, attention is being devoted to measuring VRQoL, and interest in outcomes research has grown from a recognition that patients are more interested in how interventions affect their well-being than in improvements in visual acuity [16]. The good news is that many studies have confirmed that VRQoL of patients with cataracts significantly improved after Ph-IOL [17][18][19][20][21]. In the present study, we also confirmed that after Ph-IOL, both visual acuity and utility value increased significantly.…”
Section: Discussionsupporting
confidence: 83%
“…Increasingly, attention is being devoted to measuring VRQoL, and interest in outcomes research has grown from a recognition that patients are more interested in how interventions affect their well-being than in improvements in visual acuity [16]. The good news is that many studies have confirmed that VRQoL of patients with cataracts significantly improved after Ph-IOL [17][18][19][20][21]. In the present study, we also confirmed that after Ph-IOL, both visual acuity and utility value increased significantly.…”
Section: Discussionsupporting
confidence: 83%
“…Accurate determination of ocular dominance is useful in clinical decision-making, as it relates to monovision management of presbyopia [37][38][39] with intraocular lens implant in cataract surgery, 40,41 contact lenses, 39,42 or LASIK. 43,44 The determination of ocular dominance has mainly been based on sighting dominance, which takes little time to perform.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF is a cell factor that can promote mesenchymal proliferation and division, and is derived from mesenchymal tissue such as fibroblasts, epithelial cells, and endothelial cells. PDGF functions by combining with its cell surface receptor PDGFR (Arshinoff and Bastianelli, 2011; Mancino et al, 2011;Zhang et al, 2011). It has different subtypes such as A, B, C, D, etc.…”
Section: Discussionmentioning
confidence: 99%